2002
DOI: 10.1046/j.1466-7657.2002.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of maternity care for adolescent mothers in Mbabane, Swaziland

Abstract: Early pregnancy and unplanned childbirth may have far-reaching physical, psychological and social consequences for the adolescent girl and her offspring and are therefore public health issues of concern. A number of evidence-based maternity practices might, if properly applied, prevent unnecessary health-related problems in mothers and newborns, postnatally. In order to identify the areas of maternity practice that require improvement in Swaziland, the overall aim of this study was to generate systematic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
2
8
0
2
Order By: Relevance
“…The most commonly stated age of female sexual debut was 11–13 years, compared to 14–15 years for males. This finding is consistent with other studies reported on sexual reproductive health (Mngadi 1999; Zwane 2000).…”
Section: Findings and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most commonly stated age of female sexual debut was 11–13 years, compared to 14–15 years for males. This finding is consistent with other studies reported on sexual reproductive health (Mngadi 1999; Zwane 2000).…”
Section: Findings and Discussionsupporting
confidence: 94%
“…Many researchers have demonstrated that adolescents and young adults with high levels of knowledge about STDs and HIV/AIDS continue to practise unsafe sex (Keller et al. 1996; Mngadi 1999; Ndubani 1997; Zwane 2000).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…One study examining quality of maternity care received by adolescents in Swaziland described the care provided as sub-optimal and missing many essential components (such as physical examinations, blood and urine testing), resulting in increased complications during childbirth. This was attributed to poor provider training and negligence (41). The societal stigma often associated with adolescent pregnancy may play out as reduced conscientiousness in provision of care by healthcare workers when an adolescent is involved.…”
Section: Discussionmentioning
confidence: 99%
“…26 Conhecer a evolução pré-natal contribui com o planejamento da assistência ao parto a ser desenvolvida, facilitando o processo de atenção. Além disso, tratando-se de hospital de ensino, há certa rotatividade de alunos e médicos residentes, de forma que a assistência ao parto não necessariamente é realizada pela pessoa que fez a admissão, o que ratifica a importância da qualidade dos registros nos prontuários.…”
Section: Discussionunclassified
“…A não utilização de bicos de borracha e leite artificial no alojamento conjunto e unidade neonatal evidencia o empenho institucional na promoção do aleitamento materno. 30 Investigação realizada na África do Sul evidenciou que 71% das mães foram encorajadas a amamentar precocemente, 26 situação melhor que a da maternidade estudada, já que nesta o aleitamento na primeira hora de vida foi insatisfatório tanto nos prontuários quanto nos partos observados. No mesmo serviço, em 2001, profissionais que atuavam no centro obstétrico apontaram a falta de preparo técnico para essa ação.…”
Section: Discussionunclassified